2021
DOI: 10.1186/s13046-021-01949-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive description of the current breast cancer microenvironment advancements via single-cell analysis

Abstract: Breast cancer is a heterogeneous disease with a complex microenvironment consisting of tumor cells, immune cells, fibroblasts and vascular cells. These cancer-associated cells shape the tumor microenvironment (TME) and influence the progression of breast cancer and the therapeutic responses in patients. The exact composition of the intra-tumoral cells is mixed as the highly heterogeneous and dynamic nature of the TME. Recent advances in single-cell technologies such as single-cell DNA sequencing (scDNA-seq), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 138 publications
(176 reference statements)
0
23
0
Order By: Relevance
“…Tumor microenvironment (TME), a complex ecosystem comprising of tumor cells, immune cells, and stromal populations including vascular cells and fibroblasts ( 34 , 35 ). Our data showed that vascular endothelial cells in tumors could take up sja-miR-61 secreted by tumor cells, which in turn affects the migration of vascular endothelial cells, and thereby hinders tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment (TME), a complex ecosystem comprising of tumor cells, immune cells, and stromal populations including vascular cells and fibroblasts ( 34 , 35 ). Our data showed that vascular endothelial cells in tumors could take up sja-miR-61 secreted by tumor cells, which in turn affects the migration of vascular endothelial cells, and thereby hinders tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using new and powerful technologies, such as single-cell RNA sequencing and mass cytometry, enabled shedding light on ncRNA-related dynamic changes of TME components during TNBC transformation and malignant progression [ 23 ]. The identification and the full understanding of circulating ncRNA roles in the TME could strongly help in assessing the risk of relapse and metastasis, the response to treatment and in developing new molecular targeted therapies to improve the survival in TNBC.…”
Section: Circulating Non-coding Rnas As Biomarkers In Tnbcmentioning
confidence: 99%
“…The tumor microenvironment (TME) is a complex environment composed of a variety of cell types including tumor cells, tumor stromal cells like fibroblasts, endothelial and immune cells [ 23 ]. In general, there is a crosstalk between cancer cells and the TME, therefore the TME affects the development and progression of cancer [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the use of omics data, particularly genomics, has led to insights that have been used in clinical oncology to support treatment decisions, SC analysis, which has recently emerged as a promising approach for capturing invaluable cellular-level data, such as TME and metastasis status [ 75 , 120 ]. However, it is limited by artifacts caused by evolutionary dynamics during the growth of a laboratory clone and by the fact that it can only examine a small number of founder cells [ 121 ].…”
Section: Challengesmentioning
confidence: 99%